Synthesis and Spectroscopic Characterization of Two New Dawson Sandwich Complexes: Na18[(NaOH)2(VO)2(P2W15O56)2].40H2O and Na18[(NaOH)2(VO)2(As2W15O56)2].27H2O - Mohammad Hakimi; Mohammad Reza Mohammadi; Salma Behboupour (E-Journal of Chemistry, 2012)
Reaction of the three vacant complex of a-[P2W15O56]12- and a-[As2W15O56]12- with divalent cation of VO2+ in 1:1 mole ratio yields a previously unknown sandwich-type Wells-Dawson complex; Na18[(NaOH)2(VO)2(P2W15O56)2].40H2O (represented as Na2(VO)2P4W30) and Na18[(NaOH)2(VO)2(As2W15O56)2].27H2O (represented as Na2(VO)2As4W30). These complexes contain anions in which two divalent VO2+ cations with two Na+ ions are symmetrically sandwiched between two α-[P2W15O56]12- or α-[As2W15O56]12- groups leading to a “lacunary” sandwich complex. The anion complexes are isolated as sodium salts and characterized by elemental analysis, TGA, IR, 31P NMR and UV-Vis spectroscopy.